IMPLEMENTATION OF ANGULAR JS FRAMEWORK IN DESIGN WEB-BASED ADMISSION SYSTEM APPLICATION - Eka Lia Febrianti; Ilwan Syafrinal; Agus Suryadi (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: Technology is able to digitize human work that was originally manual to become automatic and of course takes less time and better accuracy compared to results done by humans. But there are still many companies that have not implemented this technology. The use of the AngularJS framework in web application development has proven to be effective in enhancing the user experience and ease of development. In addition, the application of Agile methods in the application development process can provide the flexibility and adaptability needed to deal with frequent changes in requirements. This study aims to investigate the implementation of the AngularJS framework in the design of a web-based acceptance system application using the Agile method. The results of the study show that the implementation of the AngularJS framework in the design of web-based acceptance system applications provides significant benefits. In conclusion, the implementation of the AngularJS framework in the design of web-based acceptance system applications using Agile methods can improve efficiency, quality, and user experience. Using AngularJS enables the development of responsive and interactive applications, while the Agile method facilitates adaptation to changing customer needs. Therefore, the use of AngularJS with an Agile approach should be carefully considered by organizations wishing to develop successful web-based acceptance system applications.            Keyword s: Admissions, Agile, AngularJS, Web Abstract: Teknologi mampu mendigitalisasi pekerjaan manusia yang awalnya manual menjadi otomatis dan tentunya memakan waktu yang lebih singkat dan akurasi yang lebih baik dibandingkan dengan hasil yang dikerjakan oleh manusia. Tetapi masih banyak perusahaan perusahaan yang belum menerapkan teknologi ini. Penggunaan framework AngularJS dalam pengembangan aplikasi web telah terbukti efektif dalam meningkatkan pengalaman pengguna dan kemudahan pengembangan. Selain itu, penerapan metode Agile dalam proses pengembangan aplikasi dapat memberikan fleksibilitas dan adaptabilitas yang diperlukan untuk menghadapi perubahan persyaratan yang sering terjadi. Penelitian ini bertujuan untuk menginvestigasi implementasi framework AngularJS dalam desain aplikasi sistem penerimaan berbasis web menggunakan metode Agile. Hasil penelitian menunjukkan bahwa implementasi framework AngularJS dalam desain aplikasi sistem penerimaan berbasis web memberikan manfaat yang signifikan. Dalam kesimpulannya, implementasi framework AngularJS dalam desain aplikasi sistem penerimaan berbasis web menggunakan metode Agile dapat meningkatkan efisiensi, kualitas, dan pengalaman pengguna. Penggunaan AngularJS memungkinkan pengembangan aplikasi yang responsif dan interaktif, sementara metode Agile memfasilitasi adaptasi terhadap perubahan kebutuhan pelanggan. Oleh karena itu, penggunaan AngularJS dengan pendekatan Agile harus dipertimbangkan secara cermat oleh organisasi yang ingin mengembangkan aplikasi sistem penerimaan berbasis web yang sukses.            Keywords: Admisi, Agile, AngularJS, Web